Analysis of the Real Estate Market in Assessment of the Economy in Urban Regeneration Programs in Poland - Jadach-Sepioło, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The real estate market is rarely analysed as a component of economic assessments during the preparation of urban regeneration programs, though low real estate prices and their limited liquidity are often main reasons for a degraded area’s lack of attractiveness. The potential increase in the value of real estate may also be one of the basic motivators to engage in property revitalisation activities.The article presents the potential of the real estate market analyses in the context of delimiting degraded areas in urban regeneration programs and the attendant study of the economy.